PNPLA1-Mediated Acylceramide Biosynthesis and Autosomal Recessive Congenital Ichthyosis - Fansi Zeng; Wenzhen Qin; Feifei Huang; Pingan Chang (Metabolites, 2022)
The stratum corneum of the epidermis acts as a life-sustaining permeability barrier. Unique heterogeneous ceramides, especially ω-O-acylceramides, are key components for the formation of stable lamellar membrane structures in the stratum corneum and are essential for a vital epidermal permeability barrier. Several enzymes involved in acylceramide synthesis have been demonstrated to be associated with ichthyosis. The function of patatin-like phospholipase domain-containing protein 1 (PNPLA1) was a mystery until the finding that PNPLA1 gene mutations were involved in autosomal-recessive congenital ichthyosis (ARCI) patients, both humans and dogs. PNPLA1 plays an essential role in the biosynthesis of acylceramide as a CoA-independent transacylase. PNPLA1 gene mutations cause decreased acylceramide levels and impaired skin barrier function. More and more mutations in PNPLA1 genes have been identified in recent years. Herein, we describe the structural and functional specificity of PNPLA1, highlight its critical roles in acylceramide synthesis and skin barrier maintenance, and summarize the PNPLA1 mutations currently identified in ARCI patients.